2004
DOI: 10.2174/0929867043365143
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Constituents and Actions of Rubus Species

Abstract: Rubus species (family Rosaceae) have been cultivated for centuries for their fruits. These and other parts of the plants have been used traditionally for therapeutic purposes. This article highlights these and the potential they can offer. The constituents reported in the various species and those demonstrated to exhibit pharmacological properties have been reviewed. In the search for biologically active compounds, one of the most frequently documented species of the genus is the raspberry plant R. idaeus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 0 publications
1
100
0
6
Order By: Relevance
“…4,19,20) Despite the absence of experimental studies concerning the analgesic properties of R. rosaefolius, other plants of the Rubus genus have exhibited important antinociceptive effects in mice. 6,12) Table 1 shows that the hydroalcoholic extract and any fractions caused a pronounced effect when analysed against writhing model in mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,19,20) Despite the absence of experimental studies concerning the analgesic properties of R. rosaefolius, other plants of the Rubus genus have exhibited important antinociceptive effects in mice. 6,12) Table 1 shows that the hydroalcoholic extract and any fractions caused a pronounced effect when analysed against writhing model in mice.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] Chemical and pharmacological studies have shown that some species produce active principles that exert antigastropathic, antiinflammatory, antioxidant activity. [5][6][7] Besides these activities, it has been reported that extracts of some species of this genus are potential antimicrobial and analgesic sources.…”
mentioning
confidence: 99%
“…Some are cultivated in numerous varieties as industrial plants for the quality of nutritious and tasty fruits (Patel et al 2004). One of the varieties of Rubus is fruticosus which was introduced to official register and has been used in traditional medicine for their many medicinal properties (Alice and Campbell 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The rising number of publications in this domain demonstrated that metabolomics is not just a new "omics" but a valuable emerging tool to study phenotype and changes in phenotype caused by environmental infl uences, disease or changes in genotype (6,9,10,54,77).…”
Section: Introductionmentioning
confidence: 99%